1999
DOI: 10.3758/bf03206896
|View full text |Cite
|
Sign up to set email alerts
|

Relative area and relative luminance combine to anchor surface lightness values

Abstract: The anchoring of lightness perception was tested in simple visual fields composed of only two regions by placing observes inside opaque acrylic hemispheres. Both side-by-side and center/surround configurations were tested. The results, which undermine Gilchrist and Bonato's (1995) recent claim that surrounds tend to appear white, indicate that anchoring involves both relative luminance and relative area. As long as the area of the darker region is equal to or smaller than the area of the lighter region, relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 47 publications
7
55
1
Order By: Relevance
“…Li and Gilchrist (1999) took a clever step away from such complications by placing their observers' heads in a large illuminated hemispherical dome, the inside of which was divided into two parts, painted black and middle grey. An arrangement such as this meets the minimal conditions for perceiving a surface (Koffka, 1935, p. 111 Li and Gilchrist (1999). From "An Anchoring Theory of Lightness Perception" by A. Gilchrist, C. Kossyfidis, F. Bonato, T. Agostini, J. Cataliotti, X.…”
Section: Testing the Model: Lightness In A Domementioning
confidence: 99%
See 1 more Smart Citation
“…Li and Gilchrist (1999) took a clever step away from such complications by placing their observers' heads in a large illuminated hemispherical dome, the inside of which was divided into two parts, painted black and middle grey. An arrangement such as this meets the minimal conditions for perceiving a surface (Koffka, 1935, p. 111 Li and Gilchrist (1999). From "An Anchoring Theory of Lightness Perception" by A. Gilchrist, C. Kossyfidis, F. Bonato, T. Agostini, J. Cataliotti, X.…”
Section: Testing the Model: Lightness In A Domementioning
confidence: 99%
“…From "An Anchoring Theory of Lightness Perception" by A. Gilchrist, C. Kossyfidis, F. Bonato, T. Agostini, J. Cataliotti, X. Li, et al, 1999, Psychological Review, 106, p. 800. Copyright 1999 by the American Psychological Association.…”
mentioning
confidence: 99%
“…In order to develop a generic model that can truthfully predict PDR, sensory and cognitive processes involved in extraction of this attribute from complex stimuli need to be taken into account. Previous research has shown that the area of the brightest patches and the image topology affect the perception of lightness and contrast [17,19,26], and therefore should be considered in constructing such a PDR model. Furthermore, image contrast and colorfulness are important factors in visual perception and, based on previous findings [8,11,24,25], could be involved in the process related to the extraction of observed image attributes.…”
Section: Discussionmentioning
confidence: 99%
“…The human visual system then scales the rest to this maximum, generating an internal, scene-dependent scale of light and dark. Furthermore, Li and Gilchrist [17] observed that anchoring is affected by the relative area of the brightest patch.…”
Section: Perceived Lightnessmentioning
confidence: 99%
See 1 more Smart Citation